The impact of rainfall changes on soil bacterial and fungal communities in Pinus yunnanensis - Wang, Lin; Dong, Qiong; Zheng, Shaojie; Li, Xingze; Zeng, Huiping; Chen, Yu; Shi, Shunrou (Frontiers in Microbiology, 2025)
IntroductionTo explore the differences in soil bacterial and fungal community characteristics under Pinus yunnanensis forests with different rainfall amounts, natural Pinus yunnanensis forests in Guangnan County (GN), Jianshui County (JS), and Yuanjiang County (YJ) of Yunnan Province, China, were selected as the research objects.MethodsThree 20 × 20 standard plots were set up for each forest stand. The antioxidant system of Pinus yunnanensis seedlings in different plots was determined, and high-throughput sequencing technology was used to analyze soil bacteria and fungi.ResultsThe results showed that during the growth process of Pinus yunnanensis, the activities of SOD and POD, as well as the content of Pro, were highest in GN, while the content of SP was highest in the YJ. Significant differences were found in the α-diversity of soil bacterial and fungal communities among regions (p < 0.05). Specifically, for soil bacteria, the Shannon, Chao1, and ACE (Abundance-based Coverage Estimator) indices were highest in GN and lowest in JS; for fungi, the Chao1 and ACE indices were highest in YJ and lowest in JS. The dominant phyla of soil bacterial communities in GN and JS regions were Acidobacteria, Proteobacteria, and Chloroflexia, whereas in the YJ region were Acidobacteria, Verrucomicrobiota, and Proteobacteria. The dominant phyla of soil fungal communities across all regions were Basidiomycota and Ascomycota. Through the comparison of Tax4Fun and FUNGuild functions, it was found that more than 80% of the main functions of soil bacteria in various regions are related to metabolism. Soil fungi were primarily of the Symbiotroph nutritional functional types, and the main functional group was Ectomycorrhizal fungi. In addition, changes in rainfall had minimal effect on the functional abundance of soil bacterial communities but had a more significant impact on the functional abundance of fungal communities.DiscussionIn summary, the soil bacterial community diversity and richness index of Pinus yunnanensis in the GN region is the highest, and the bacterial phylum related to plant growth and Symbiotroph fungi account for the highest proportion. This study elucidated the response mechanism of Pinus yunnanensis to changes in rainfall from a microbial perspective, providing a theoretical basis for their growth being regulated by rainfall.